Driving Customer Loyalty through the Service Marketing Mix (7P): The Mediating Role of Customer Satisfaction - Raymond Piring; Cliford Racelino Ratulangi; Lazarus Vianney; Mandianus Buge; Yulianus Logo (Al-Qalam Institue, 2026)
This study aims to synthesize the existing literature on the role of the Service Marketing Mix (7P) in influencing customer satisfaction and customer loyalty within service industries. A qualitative research design employing a literature review approach was adopted to critically analyze and integrate findings from peer-reviewed journal articles, academic books, and other scholarly publications related to marketing management. The collected literature was systematically examined through data condensation, data display, and conclusion verification to identify conceptual patterns and relationships among the research variables. The findings indicate that all seven dimensions of the Service Marketing Mix—Product, Price, Place, Promotion, People, Process, and Physical Evidence—contribute to customer satisfaction, although their relative influence varies across service contexts. Among these dimensions, People and Process consistently emerge as the most influential factors due to their direct impact on service delivery and customer experience. Furthermore, the review confirms that customer satisfaction functions as a key mediating mechanism linking the implementation of the Service Marketing Mix to customer loyalty. The study contributes to marketing literature by providing an integrated conceptual framework that enhances the theoretical understanding of service marketing and offers practical guidance for designing sustainable customer loyalty strategies.